Pengaruh Pertumbuhan Aset dan Beban Bunga terhadap Profit Bank Milik Pemerintah Indonesia - Syaputri, Ayu Geby Gisela (Forum Bisnis Kewirausahaan, 2024)
The purpose of this study was to determine the effect of asset growth and interest expense on the profit of Indonesian state-owned banks. The observation period is from January to December 2022. This study uses multiple regression analysis. In this study it was concluded that asset growth had a negative and significant effect on the profits of Indonesian state-owned banks, while interest expense had a positive and significant effect on the profits of Indonesian government-owned banks.